Influence of Diet on the Effect of the Probiotic Lactobacillus paracasei in Rats Suffering From Allergic Asthma - Xie, Ao; Song, Jiaping; Lu, Shan; Liu, Yinhui; Tang, Li; Wen, Shu (Frontiers in Microbiology, 2021)
Mounting evidence suggests that probiotics can be used to treat allergic asthma by modulating the gut microbiota, and that the effects of probiotics may be influenced by environmental factors such as diet. We conducted a rat model with allergic asthma (AA) modulated by Lactobacillus paracasei, feeding up with high-fat or high-fiber diets based on collecting data from 85 questionnaires. The systemic proinflammatory cytokines were detected by ELISA and overall structure of fecal microbiota were analyzed via 16S rRNA gene sequencing. The results showed consumption of a high-fiber diet alleviated the allergic symptoms and airway inflammation, and lead to improve the the imbalance of T-helper type 1 (Th1)/Th2 cells with increased expression of interferon-γ and decreased expression of interleukin-4. Whereas, the high-fat diet had deteriorating implications and skewed the inflammatory perturbation. Furthermore, abundances of families Lachnospiraceae, Ruminococcaceae and Desulfovibrionaceae, genera Blautia, unidentified_Ruminococcaceae, unidentified_Clostridiales and Oscillibacter were enriched in L. paracasei-modulating rats fed with high-fiber diet. Phylum Bacteroidetes, Actinobacteria, families Muribaculaceae, Tannerellaceae, Prevotellaceae, Enterococaceae, Bifidobacteriaceae and Peptostreptococcaceae, genera Allobaculum, Parabacteroides, Enterococcus, Bifidobacterium, Turicibacter and Romboutsia were in relatively high abundance in the rats administered high-fat diet. Association between changed microbiota and inflammatory cytokines was also conferred. These data indicated that the efficacy of L. paracasei in allergic asthma was influenced by different dietary patterns. Hence, diet is important for probiotic therapy when managing allergic asthma.